2016
DOI: 10.5897/ajpp2015.4358
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties of antiepileptic drugs levetiracetam and clonazepam in mice brain after in vitro-induced oxidative stress

Abstract: This study aimed to investigate the in vitro antioxidant activity of the novel anticonvulsant levetiracetam and benzodiazepine clonazepam. To do this, the mice brain homogenates were incubated with levetiracetam (50, 100 or 200 g/ml) or clonazepam (50, 100 or 200 g/ml), and then, submitted to heating at 37°C for 1 h. Ascorbic acid (vitamin C, 200 g/ml) was used as reference antioxidant drug. The markers of oxidative stress, such as lipid peroxidation, nitrite-nitrate content, catalase activity, and reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Some studies have shown that antiepileptic drugs can turn redox status of organism toward to favourable form in patient with epilepsy. [35][36][37] Thus, we may have found this balance unchanged in patient group for 2 reasons: 1) antiepileptic drugs may affect this balance favorably, or 2) serum samples were taken during seizure-free period.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have shown that antiepileptic drugs can turn redox status of organism toward to favourable form in patient with epilepsy. [35][36][37] Thus, we may have found this balance unchanged in patient group for 2 reasons: 1) antiepileptic drugs may affect this balance favorably, or 2) serum samples were taken during seizure-free period.…”
Section: Discussionmentioning
confidence: 98%
“… 8 - 10 In contrast, others showed a protection effect of LEV against oxidative stress in animal models. 11 , 12 On the other hand, some studies showed no effect of these agents on oxidative stress activity. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…Several classes of approved drugs have been studied through the years for their antioxidant properties [ 1 , 5 , 6 ]. Proton pump inhibitors [ 7 ], antidiabetics [ 8 ], drugs acting on the cardiovascular system [ 9 ], antiepileptics [ 10 ], and anti-inflammatory agents [ 11 ] represent some of the investigated classes, which are also paired by antioxidant natural and semi-synthetic compounds with biological activity [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Furthermore, besides therapeutic agents, it must be stressed that bioactive components from diet have been recognized among the risk factors or, on the other hand, protective agents possibly influencing oxidative stress and pathogenesis of related diseases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%